Stories in scripture and inscriptions : comparative studies on narratives in Northwest Semitic inscriptions and the Hebrew Bible - Parker, Simon B. (Oxford University Press, 1997)
This book compares a variety of biblical narratives with the stories found in several Northwest Semitic inscriptions from the ancient kingdom of Judah and its contemporary Syro-Palestinian neighbors. In genre, language, and cultural context, these epigraphic stories are closer to biblical narratives than any other ancient Near Eastern narrative corpus. For the first time, Parker analyzes and appreciates these stories as narratives and sets them beside comparable biblical stories. He; illuminates the narrative character and techniques of both epigraphic and biblical stories and in many cases reveals their original social context and purpose. In some cases, he is able to shed light on the question of the sources and composition of the larger work in which most of the biblical; stories appear, the Deuteronomistic history. Against the claim that the genius of biblical prose narrative derives from the monotheism of the authors, he shows that the presence or absence of a divine role in each type of story is consistent throughout both biblical and epigraphic examples, and that, when present, the role of the deity is essentially the same both inside and outside the Bible, inside and outside Israel.